Aviation's emissions and contribution to the air quality in China. (15th March 2019) - Bo, Xin; Xue, Xiaoda; Xu, Jun; Du, Xiaohui; Zhou, Beihai; Tang, Ling
Abstract: With a rapid increase in air traffic, aviation has become an increasingly important contributor to anthropogenic air pollutants (particularly nitrogen oxides (NOX )) over China. This study provides the first overall estimation of the aviation emissions from all civil airports in mainland China as well as the associated contribution to ambient air quality. First, aircraft emissions (NOx, sulfur dioxide (SO2 ), carbon monoxide (CO), hydro-carbons (HC), particulate matter (PM2.5 and PM10 ), volatile organic carbons (VOCs) and black carbon (BC)) during landing and take-off cycles (below 3 km) are estimated for both recent (2000–2016) and future (2020) scenarios. Second, the corresponding environmental impacts are measured by the Comprehensive Air Quality Model with extensions (CAMx). The results have insightful policy implications for China's aviation planning. (1) Generally, China's aviation emissions and their effect on air quality have been and will continue to increase. (2) Among species, NOx dominated China's aircraft emissions in terms of both emission amount and environmental impact, while PM2.5 generated an extensive influence. (3) With respect to spatial distribution, the air quality effect was highly concentrated at emission-intense airports that served economic zones and/or tourist spots. Highlights: China's aviation emissions are estimated for 2000–2016 and 2020 scenarios. The corresponding environmental contribution is calculated via the CAMx model. Aviation emissions and environmental impact both followed an upward trend. The airports serving economic zones and/or tourist spots made a high contribution. Aviation emissions impacted NOx to a large extent and PM2.5 in a broad domain.